Semantics Analysis of Hyponymy on “Hank and The Horse” Short Story on Youtube - Paramita Kusumawardhani (ITScience (Information Technology and Science), 2021)
This study aimed to know about the use and the most dominant of hyponymy as the semantics features through a story Hank and The Horse. In linguistics, a hyponym is a word or phrase whose semantic field is included within another term, its hypernymy. A hyponym shares a type-of relationship with its hypernymy. Hyponymy is part of semantics, and it is sometimes referred to as meaning inclusion. The research was done by using short stories on YouTube. Technology development has been very significant lately, making it easy for educators to find sources for teaching, learning, and other activities. One of them is a short story. Many short stories on YouTube can be used as the teaching-learning media, depending on the subject that is going to discuss. The method in this research was descriptive qualitative methods in presenting the results. Data were analyzed based on the association with hyponyms by semantic analysis. The study participants were the 5th-semester students of the University of Bina Sarana Informatika. The hyponymy was classified into nouns, pronouns, adverbs, verbs, and adjectives, with a total, were 40 hyponymies. The study's findings were 40 hyponymies found in the short story, then classified into nouns, pronouns, adverbs, verbs, and adjectives. Then they were divided into: (1). 13 nouns; (2). 4 pronouns; (3). 7 adverbs; (4). 12 verb; and (5). 4 adjective and the most dominant is hyponymy in the noun.